MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL GROUP INVESTIGATION BERBANTUAN VIDEO PADA SISWA SEKOLAH DASAR - Lasfeto, Angelique Rabeka (Jurnal Penelitian dan Pengembangan Pendidikan, 2017)
This study aims to determine the improvement of student learning outcomes through video-assisted group investigation model. This type of research is a classroom action research with the subject of research is the students of grade V SD N 4 Kaliuntu as many as 38 people. Data collection in this research is done by test method in the form of multiple choice. The data that have been obtained is then analyzed using quantitative descriptive statistical analysis method. The results of this study indicate that in the first cycle the average learning outcome of IPA of 70.02 has increased by 10.5 in cycle II to 80.07. While for the students' completeness score in the first cycle of 76.31% of the students who numbered 38 people only thoroughly for 29 people. And the increase in cycle II of 7.89% to 84.21% and students experiencing completeness in learning as many as 32 people from 38 people. The results of this study indicate that student learning outcomes can be increased through the video-assisted group investigation model